Pengaruh Bahan Ajar Pendidikan Jasmani Terintegrasi dengan ISMUBA Bagi Siswa SD Muhammadiyah - Agung Widodo; Muhammad Thariq Aziz (STKIP Muhammadiyah Kuningan, 2019)
This study aims to determine the impact of the use of Physical Education teaching materials that are integrated with Al-Islam Kemuhammadiyahan Arabic (ISMUBA). The study sample was 19 students of class I of Muhammadiyah 1 Elementary School in Sukaraja (Muturaja) and 16 people of Elementary School ‘Aisyiyah of Sukabumi City. The research method used pre-experimental with one group pre test-posttest design. The treatment given is teaching using ISMUBA integrated physical education teaching materials. Data collection techniques with tests and observations. The data analysis technique with paired t-test was preceded by the prerequisite test, namely the normality and homogeneity test with the mini tab software. The results of the Muturaja School normality test pre-test obtained p-value 0.150> 0.05 and post-test obtained p-value 0.150> 0.05 while 'Aisyiyah School pre-test obtained p-value 0.051> 0.05 and post-test obtained p-value 0.150> 0.50, meaning that data is normally distributed. The results of the Muturaja School homogeneity test obtained p-value 0.821> 0.05 and ‘Aisyiyah School obtained p-value 0.452> 0.05, proving that the sample was homogeneous. Test the hypothesis with table t at a significant level = 0.05 at Muturaja School obtained t count = 12.90 and ‘Aisyiyah School t count = 18.82. Because t count> t table, the null hypothesis (H0) is rejected and the alternatif hypothesis (Ha) is accepted. Thus it can be concluded that there is the influence of Physical Education teaching materials integrated with ISMUBA on the learning outcomes of class I students of Muturaja Elementary School and ‘Aisyiyah Elementary School Academic Year 2018/2019.